2008
DOI: 10.1139/f08-172
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial carbon contribution to lake food webs: could the classical stable isotope approach be misleading?

Abstract: Carbon stable isotope analyses have been widely used to estimate terrestrial carbon contribution to lake secondary production. In such approaches, phytoplankton is tacitly assumed as a single, isotopically homogenous source. Such assumption might be valid if (i) zooplankton do not feed selectively on specific algal taxa within bulk phytoplankton, or (ii) although zooplankton do feed selectively, the variability in the d 13 C values amongst the different algal taxa is small compared with the variability between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…Proposed explanation of obtained results remains in accordance with other studies aimed to explain what happens with terrestrial organic matter in aquatic ecosystems . It is worth of note that after higher river inflow the δ 13 C signature in rotifer‐dominated fraction of zooplankton in the Dobczyce Reservoir tended towards the value characteristic of terrestrial C 3 plants in northern latitudes , which points to the terrestrial origin of incorporated carbon . The coinciding high development of rotifers might be explained by their use of allochthonous fine POM or bacteria developing on these particles .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Proposed explanation of obtained results remains in accordance with other studies aimed to explain what happens with terrestrial organic matter in aquatic ecosystems . It is worth of note that after higher river inflow the δ 13 C signature in rotifer‐dominated fraction of zooplankton in the Dobczyce Reservoir tended towards the value characteristic of terrestrial C 3 plants in northern latitudes , which points to the terrestrial origin of incorporated carbon . The coinciding high development of rotifers might be explained by their use of allochthonous fine POM or bacteria developing on these particles .…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies to assess the sources and transformation of organic matter using stable isotopes have been used to examine the paths of carbon in lake food webs . Indeed studies on lacustrine zooplankton and benthic organisms have shown their importance in transmission of terrestrial organic matter into aquatic ecosystems , and a strong correlation in the stable isotope signature in the zooplankton and the stable isotope signature of POM .…”
Section: Introductionmentioning
confidence: 99%
“…Also, we assumed that all phytoplankton taxa were isotopically similar. If certain taxa were δ 13 Cenriched and preferentially consumed by invertebrates, then we may overestimate the role of terrestrial-derived POM in the food web (Perga et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton stable isotope signature has rarely been measured directly (Grey, Jones, & Sleep 2000) as phytoplankton cells are difficult to isolate from other particles (bacteria, heterotrophic protists and detritus of different origins) that compose the bulk particulate organic matter. In addition, in SIA studies, phytoplankton is usually tacitly considered as a single, isotopically homogenous dietary source but the isotopic heterogeneity within the phytoplankton community was recently shown to be a potential source of overestimation of terrestrial C contribution to lake food webs (Perga, Kainz, & Mazumder 2008).…”
Section: Introductionmentioning
confidence: 99%